Adiposity Markers as Predictors of 11-Year Decline in Maximal Walking Speed in Late Midlife. (September 2021) - Wennman, Heini; Jerome, Gerald J.; Simonsick, Eleanor M.; Sainio, Päivi; Valkeinen, Heli; Borodulin, Katja; Stenholm, Sari
Background: Obesity is linked to poorer physical functioning in older adults, but impact of excess adiposity on loss of functional capacity in late midlife is unclear. This study examined associations between adiposity markers and 11-year change in maximal walking speed, a sensitive indicator of physical functioning, among adults aged 55 to 69 years.Method: Maximal walking speed over 6.1 m was assessed in 2000 and 2011 among Finnish men ( n = 409) and women ( n = 498) from the prospective Health 2000 Survey. Body mass index (BMI) and waist circumference were assessed in 2000. Generalized estimating equation models estimated changes in maximal walking speed by BMI and waist circumference, stratified by sex.Results: BMI greater than 30 kg/m 2 was associated with accelerated decline in maximal walking speed particularly in women. Associations with waist circumference were nonsignificant.Conclusion: Late midlife obesity may speed up the decline in functional capacity as measured by maximal walking speed, especially in women.